Synergetic effect of silver nanoplate and magnetic field on photon upconversion based on sensitized triplet-triplet annihilation in polymer system - Noda, Y. (Institute of Physics Publishing, 2020)
Effects of silver nanoplate (AgPL) and magnetic field on photon upconversion based on sensitized triplet-triplet annihilation (PUC-TTA) were examined in the system of platinum(II) octaethylporphyrin (PtOEP) and 9,10-diphenylanthracene (DPA), when AgPLs were incorporated into polymer thin films containing PtOEP and DPA. In the presence of AgPL, the PUC emission intensity increased as compared with that in the absence of AgPL. The result is most likely attributable to the localized surface plasmon resonance of AgPL. On the other hand, in the absence of AgPL, the PUC emission intensity decreased in the presence of magnetic field, while in the presence of AgPL, the PUC emission intensity increased drastically in the presence of magnetic field. The synergetic effect of AgPL and magnetic field on the PUC emission intensity in PUC-TTA was observed for the first time. Â© 2019 The Japan Society of Applied Physics.